Imaging label-free intracellular structures by localisation microscopy - Kaufmann, Rainer; Müller, Patrick; Hausmann, Michael; Cremer, Christoph (Micron, 2011)
Localisation microscopy methods allow to realize a light optical resolution far beyond the Abbe-Rayleigh limit of about 200nm laterally and 600nm axially. So far, this progress was achieved using labelling with appropriate fluorochromes and fluorescent proteins. Here, we describe for the first time that optical resolution of cellular structures in the λ/10 range (∼50nm) can be achieved even in label-free cells. This was obtained using Spectral Precision Distance/Position Determination Microscopy (SPDM), a method based on the general principles of localisation microscopy. Besides a substantial resolution improvement of autofluorescent structures, SPDM revealed cellular objects which are not detectable under conventional fluorescence imaging conditions.
Available online 28 May 2010
Gesehen am 25.07.2022